Effect of a Digital Intervention on Depressive Symptoms in Patients With Comorbid Hypertension or Diabetes in Brazil and Peru: Two Randomized Clinical Trials - Araya, Ricardo (2021)
IMPORTANCE: Depression is a leading contributor to disease burden globally. Digital mental health interventions can address the treatment gap in low- and middle-income countries, but the effectiveness in these countries is unknown. OBJECTIVE: To investigate the effectiveness of a digital intervention in reducing depressive symptoms among people with diabetes and/or hypertension. DESIGN, SETTING, AND PARTICIPANTS: Participants with clinically significant depressive symptoms (Patient Health Questionnaire-9 [PHQ-9] score ≥10) who were being treated for hypertension and/or diabetes were enrolled in a cluster randomized clinical trial (RCT) at 20 sites in São Paulo, Brazil (N=880; from September 2016 to September 2017; final follow-up, April 2018), and in an individual-level RCT at 7 sites in Lima, Peru (N=432; from January 2017 to September 2017; final follow-up, March 2018). INTERVENTIONS: An 18-session, low-intensity, digital intervention was delivered over 6 weeks via a provided smartphone, based on behavioral activation principles, and supported by nurse assistants (n = 440 participants in 10 clusters in São Paulo; n = 217 participants in Lima) vs enhanced usual care (n = 440 participants in 10 clusters in São Paulo; n = 215 participants in Lima). MAIN OUTCOMES AND MEASURES: The primary outcome was a reduction of at least 50% from baseline in PHQ-9 scores (range, 0-27; higher score indicates more severe depression) at 3 months. Secondary outcomes included a reduction of at least 50% from baseline PHQ-9 scores at 6 months. RESULTS: Among 880 patients cluster randomized in Brazil (mean age, 56.0 years; 761 [86.5%] women) and 432 patients individually randomized in Peru (mean age, 59.7 years; 352 [81.5%] women), 807 (91.7%) in Brazil and 426 (98.6%) in Peru completed at least 1 follow-up assessment. The proportion of participants in São Paulo with a reduction in PHQ-9 score of at least 50% at 3-month follow-up was 40.7% (159/391 participants) in the digital intervention group vs 28.6% (114/399 participants) in the enhanced usual care group (difference, 12.1 percentage points [95% CI, 5.5 to 18.7]; adjusted odds ratio [OR], 1.6 [95% CI, 1.2 to 2.2]; P = .001). In Lima, the proportion of participants with a reduction in PHQ-9 score of at least 50% at 3-month follow-up was 52.7% (108/205 participants) in the digital intervention group vs 34.1% (70/205 participants) in the enhanced usual care group (difference, 18.6 percentage points [95% CI, 9.1 to 28.0]; adjusted OR, 2.1 [95% CI, 1.4 to 3.2]; P < .001). At 6-month follow-up, differences across groups were no longer statistically significant. CONCLUSIONS AND RELEVANCE: In 2 RCTs of patients with hypertension or diabetes and depressive symptoms in Brazil and Peru, a digital intervention delivered over a 6-week period significantly improved depressive symptoms at 3 months when compared with enhanced usual care. However, the magnitude of the effect was small in the trial from Brazil and the effects were not sustained at 6 months